Answer:
(a) False
(b) Fase
(c) True
Step-by-step explanation:
(a) [tex](A + B) ^ 2 = (A + B) (A + B) = AA + AB + BA + BB = A ^ 2 + AB + BA + B ^ 2[/tex]. Since AB does not necessarily equal BA, we cannot say that [tex]AB + BA = 2AB[/tex] or [tex]AB + BA = 2BA.[/tex]
(b) Since AB does not necessarily equal BA, we cannot say that [tex]ABA = AAB = A ^ 2B[/tex] or [tex]ABA = BAA = BA ^ 2 = A ^ 2B.[/tex].
(c) Since [tex]ABAB = (AB) (AB) = (AB) ^ 2[/tex], then we can state that [tex]ABAB = (AB) ^ 2[/tex].